El arbol de Pablo - Mora, Pat.; Lang, Cecil (New York : Scholastic Inc., 1996)
Each year on his birthday, a young Mexican American boy looks forward to seeing how his grandfather has decorated the tree he planted on the day the boy was adopted.
Translation of: Pablo's tree.
Keywords: Birthdays -- Fiction; Mexican Americans -- Fiction; Grandfathers -- Fiction; Adoption -- Fiction; Spanish language materials